2017
DOI: 10.29252/ijrm.15.9.583
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum uric acid level and maternal and neonatal complications in preeclamptic women: A cross-sectional study

Abstract: Background: Preeclampsia is associated with maternal and neonatal complications. It has been indicated that increased uric acid might have a predictive role on preeclampsia. Objective: We aimed to investigate the relationship between the level of uric acid with maternal and neonatal complications in women with preeclampsia. Materials and Methods: In this cross-sectional study, 160 singleton preeclamptic women at more than 28 wk gestational age were included. Hemoglobin, hematocrit, platelet count, liver and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
(26 reference statements)
0
11
0
2
Order By: Relevance
“…This increased amount of serum uric acid amongst clients with preeclampsia has been reported by several studies and this increased amount is thought to correlate with the severity of the disease condition. 5,10,20,21 Antenatal patients with renal disease were excluded from taking part in this study and as such, it is unlikely that renal disease would have contributed to the higher levels of serum uric acid amongst the study population.…”
Section: Discussionmentioning
confidence: 99%
“…This increased amount of serum uric acid amongst clients with preeclampsia has been reported by several studies and this increased amount is thought to correlate with the severity of the disease condition. 5,10,20,21 Antenatal patients with renal disease were excluded from taking part in this study and as such, it is unlikely that renal disease would have contributed to the higher levels of serum uric acid amongst the study population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence rate of adverse maternal and neonatal outcomes (premature delivery, caesarean delivery, postpartum hemorrhage, neonatal asphyxia and perinatal death) in the combination group were significantly lower than that in the magnesium sulfate group. A large number of studies on the treatment of HDCP have confirmed that magnesium sulfate combined with other antihypertensive drugs is more effective in preventing ADR of patients with HDCP and improving maternal and neonatal outcomes (2325).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported elevated uric acid levels in pregnancies complicated by preeclampsia and thus of good diagnostic and prognostic value for fetus [9] [26]…”
Section: Discussionmentioning
confidence: 99%